The Influence of Digital Marketing on Generation Z's Purchase Intention Toward Green Products: The Mediating Roles of Green Brand Trust and Brand Image at The Body Shop Bandung Indonesia - Miranda Oktaviani; Arry Widodo; Nurafni Rubiyanti (Best Journal of Administration and Management, 2026)
This conceptual paper examines the influence of digital marketing strategy on Generation Z’s purchase intention toward green products at The Body Shop Indonesia, with green brand trust and brand image positioned as mediating variables. The study develops an integrated conceptual framework grounded in the Stimulus–Organism–Response (S-O-R) framework and Signalling Theory to explain how digital marketing activities shape consumer behavioral intentions through psychological mechanisms. In this framework, digital marketing strategy functions as the external stimulus, while green brand trust and brand image represent internal organismic responses that influence purchase intention as the behavioral outcome. The paper also proposes both parallel and serial mediation relationships between green brand trust and brand image in explaining sustainable consumer behavior among Generation Z. The conceptual analysis suggests that credible and sustainability-oriented digital marketing communication can strengthen consumer trust, enhance positive brand image, and ultimately increase purchase intention toward environmentally friendly products. Furthermore, green brand trust is proposed as a stronger foundational mechanism that subsequently reinforces brand image. This study contributes to the green marketing and consumer behavior literature by offering an integrated conceptual model that combines cognitive, emotional, and behavioral dimensions within the context of sustainable digital marketing. The framework also provides managerial insights for ethical brands in designing authentic digital communication strategies to engage environmentally conscious Generation Z consumers in emerging markets.